Evaluation of Imprint Cytology of Endoscopic Gastric Mucosa Biopsy in the Diagnosis of Helicobacter pylori Infection - Ali Hamid, Karima Ali; Malik, Mohamed Ibrahim Mohamed; Mukhtar, Nada Suliman Haj; Talha, Albadawi Abdelbage; Hamid, Yousif AbdAL; Abakar, Adam Dawoud (Gezira Journal of Health Sciences; Vol 14 No 1 (2018), 2018)
Background: Helicobacter pylori colonization of the gastric mucosa is associated with the pathogenesis of gastritis, peptic ulcer disease, and gastric malignancy. There are several methods to detect the presence of Helicobacter pylori .These tests include noninvasive method (serology, urea breath test, or stool antigen test) and invasive methods, such as, culture, histological examination, and rapid urease test. Method: This descriptive prospective cross sectional study was conducted in Gezira state in Wad Madeni from March - August 2016;it aimed to determine the sensitivity, specificity, positive (PPV), and negative predictive values (NPV) of imprint cytology in the detection of H. pylori compared with stool Ag test. H.pylori stool Ag test was done for 50 clinically suspected patients for H.pylori infection and one gastric biopsy from each patient was collected during endoscopy. Air-dried imprint smears of gastric biopsies were stained by the Diff-Quik method and examined for H.pylori . The presence of inflammation and intestinal metaplasia were documented. Results: The H. pylori prevalence was 38% by stool Ag test and 42% by imprint cytology. The sensitivity and specificity of imprint cytology in the detection of H. pylori were 89.5% and 87.1% respectively. The PPV and NPV were 80.1% and 93.1%, respectively. The accuracy of the test was 88.0%. Conclusion: This study concludes that gastric imprint smears stained with Diff-Quik method is a rapid, cheap, and reliable method for the detection of H.pylori infection.It recommends the use of Imprint cytology for detection of Helicobacter pylori inpatients undergoing upper gastrointestinal endoscopy.